Oxytocin-Induced Changes in Intrinsic Network Connectivity in Cocaine Use Disorder: Modulation by Gender, Childhood Trauma, and Years of Use - Joseph, Jane E.; Vaughan, Brandon K.; Camp, Christopher C.; Baker, Nathaniel L.; Sherman, Brian J.; Moran-Santa Maria, Megan; McRae-Clark, Aimee; Brady, Kathleen T. (Frontiers in Psychiatry, 2019)
Cocaine use disorder (CUD) is a major public health concern with devastating social, economic and mental health implications. A better understanding of the underlying neurobiology and phenotypic variation in individuals with CUD is necessary for the development of effective and targeted treatments. In this study, 39 women and 54 men with CUD completed a 6-minute resting state fMRI scan after intranasal oxytocin or placebo administration. Graph-theory network analysis was used to quantify functional connectivity changes due to oxytocin in striatum, anterior cingulate (ACC), insula and amygdala nodes of interest. Oxytocin increased connectivity in the right ACC and left amygdala in males whereas oxytocin increased connectivity in the right ACC and right accumbens in females. Machine learning was then used to associate treatment response (placebo minus oxytocin) in nodes of interest with years of cocaine use and severity of childhood trauma separately for males and females. Childhood trauma and years of cocaine use were associated with oxytocin-induced changes in ACC connectivity for both men and women, but connectivity changes in the amygdala were associated with years of cocaine use in men and connectivity changes in the right insula were associated with years of cocaine use in women. These findings suggest that salience network nodes (anterior cingulate and insula) are potential oxytocin treatment targets in CUD, with the amygdala as a treatment target for men and the accumbens as a treatment target for women.